Failure to expand the motor unit size to compensate for declining motor unit numbers distinguishes sarcopenic from non‐sarcopenic older men. (23rd March 2018) - Piasecki, M.; Ireland, A.; Piasecki, J.; Stashuk, D. W.; Swiecicka, A.; Rutter, M. K.; Jones, D. A.; McPhee, J. S.
Abstract : Key points: The age‐related loss of muscle mass is related to the loss of innervating motor neurons and denervation of muscle fibres. Not all denervated muscle fibres are degraded; some may be reinnervated by an adjacent surviving neuron, which expands the innervating motor unit proportional to the numbers of fibres rescued. Enlarged motor units have larger motor unit potentials when measured using electrophysiological techniques. We recorded much larger motor unit potentials in relatively healthy older men compared to young men, but the older men with the smallest muscles (sarcopenia) had smaller motor unit potentials than healthy older men. These findings suggest that healthy older men reinnervate large numbers of muscle fibres to compensate for declining motor neuron numbers, but a failure to do so contributes to muscle loss in sarcopenic men. Abstract: Sarcopenia results from the progressive loss of skeletal muscle mass and reduced function in older age. It is likely to be associated with the well‐documented reduction of motor unit numbers innervating limb muscles and the increase in size of surviving motor units via reinnervation of denervated fibres. However, no evidence exists to confirm the extent of motor unit remodelling in sarcopenic individuals. The aim of the present study was to compare motor unit size and number between young ( n  = 48), non‐sarcopenic old ( n  = 13), pre‐sarcopenic ( n  = 53) and sarcopenic ( n  = 29) men. Motor unit potentials (MUPs) were isolated from intramuscular and surface EMG recordings. The motor unit numbers were reduced in all groups of old compared with young men (all P  < 0.001). MUPs were higher in non‐sarcopenic and pre‐sarcopenic men compared with young men ( P  = 0.039 and 0.001 respectively), but not in the vastus lateralis of sarcopenic old ( P  = 0.485). The results suggest that extensive motor unit remodelling occurs relatively early during ageing, exceeds the loss of muscle mass and precedes sarcopenia. Reinnervation of denervated muscle fibres probably expands the motor unit size in the non‐sarcopenic and pre‐sarcopenic old, but not in the sarcopenic old. These findings suggest that a failure to expand the motor unit size distinguishes sarcopenic from pre‐sarcopenic muscles. Key points: The age‐related loss of muscle mass is related to the loss of innervating motor neurons and denervation of muscle fibres. Not all denervated muscle fibres are degraded; some may be reinnervated by an adjacent surviving neuron, which expands the innervating motor unit proportional to the numbers of fibres rescued. Enlarged motor units have larger motor unit potentials when measured using electrophysiological techniques. We recorded much larger motor unit potentials in relatively healthy older men compared to young men, but the older men with the smallest muscles (sarcopenia) had smaller motor unit potentials than healthy older men. These findings suggest that healthy older men reinnervate large numbers of muscle fibres to compensate for declining motor neuron numbers, but a failure to do so contributes to muscle loss in sarcopenic men.